2021
DOI: 10.2147/dddt.s240866
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy and Safety of Abrocitinib as a Treatment Option for Atopic Dermatitis: A Short Report of the Clinical Data

Abstract: Atopic dermatitis (AD) is a chronic, pruritic, inflammatory skin disease that predominantly affects children. However, it can persist in adulthood and/or start at older ages. Both dysfunction of the epidermal barrier and immune dysregulation are known to play a role in the pathogenesis of AD. In the last years, numerous studies showed that Janus kinase (JAK) enzymes have a key role in AD pathogenesis. Therefore, oral and topical JAK inhibitors are new emerging treatments for AD. We report the data relating to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“… 8 , 13 , 27 , 30 , 34 , 35 These changes were also registered in a phase IIb trial, which included adult patients suffering from moderate-to-severe forms of AD, and also reporting better results for the 200 mg per dose oral abrocitinib, for all patient-reported outcomes. 30 , 33 , 35 …”
Section: Resultsmentioning
confidence: 99%
“… 8 , 13 , 27 , 30 , 34 , 35 These changes were also registered in a phase IIb trial, which included adult patients suffering from moderate-to-severe forms of AD, and also reporting better results for the 200 mg per dose oral abrocitinib, for all patient-reported outcomes. 30 , 33 , 35 …”
Section: Resultsmentioning
confidence: 99%
“…Abrocitinib, a small-molecule inhibitor of JAK1, has been approved for the treatment of moderate-to-severe atopic dermatitis ( 10 , 11 ). As mentioned in the reviewed paper, phase III clinical trials have demonstrated the effectiveness of abrocitinib in the treatment of moderate-to-severe atopic dermatitis ( 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…284,285,287,[528][529][530] Furthermore, the rapid improvement of pruritus produced by abrocitinib supports treatment compliance, which further validates the safety and tolerability of abrocitinib in patients with moderate-to-severe AD. 531 Abrocitinib has manageable safety, and its common adverse events include nausea, headache, acne and reduced platelet counts. 532,533 Therefore, its benefit-to-harm ratio needs to be thoroughly investigated before it can be used for the long-term treatment of AD.…”
Section: (Covid-19mentioning
confidence: 99%